Perlindungan Anak dari Pernikahan Dini: Formulasi Edukasi Seksual Komprehensif Perspektif Hukum Islam dan Negara - Mujennih Mujennih; Dymas Reyhan M; Anggiana Puspa Rukmana Sihotang; David Yasir Abdillah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Material Objectives Early marriage and low understanding of sexual education are still common problems among adolescents. The contributing factors include low education, promiscuity, family economic conditions, and lack of knowledge about reproductive health. This community service activity aims to improve students' understanding of preventing ear marriage and sexual education based on national and Islamic law. The research method used is Student Centered Learning (SCL) through the Deep Learning approach, case studies, and collaborative learning. The results of the activity show an increase in students' understanding of the age limit for marriage, child protection, the impact of early marriage, the dangers of sexual harassment, and the concepts of baligh and rusyd in Islam. Sexual education integrated with Islamic law and values has proven effective in increasing students' awareness, critical thinking skills, and preventive attitudes towards early marriage and sexual violence. Conclusion Sexual education plays a very important role in efforts to prevent early marriage and sexual harassment. Through sexual education based on positive law and Islamic values, adolescents can understand reproductive health, social boundaries, their rights, and the importance of maintaining self-respect.